The gestalt approach & Eye witness to therapy - Perls, Frederick S.; Perls, Frederick S. (New York Bantam Books, 1973)
'The Gestalt Approach' and 'Eye Witness to Therapy' can be read together as one entity and also as two separate works. This book is an exploration of a somewhat new approach to the entire subject of human behavior- both in its actuality and its potentiality. It is written from the belief that man can live a fuller, richer life than most of us now do. It is written from the conviction that man has not yet even begun to discover the potential of energy and enthusiasm that lies in him. The book endeavors to bring together a theory and a practical application of that theory of the problems of daily life and to the techniques of psychotherapy. The theory itself is grounded in experience and observation; it has grown and changed with years of practice and application.--From Introduction.
Pt. I, The Gestalt approach: -- Foundations: Gestalt psychology; Homeostasis; The holistic doctrine; Contact boundary; -- Neurotic Mechanisms: Birth of neurosis; Introjection; Projection; Confluence; Retroflection; -- Here comes the neurotic -- Here and now therapy -- Peeling the onion -- Shuttling, psychodrama and confusion -- Who is listening? -- Pt. II, Eye witness to therapy: -- Gestalt in action: What is Gestalt?; Awareness; Marriage; Gestalt prayer; Couples no.1; Couples no.2; Memory and pride; Philosophy of the obvious; Madeline's dream; Everything is aware process; Fritz, friend and Freud.
Two books on which the author was working at the time of his death, published as one.
Keywords: Gestalt therapy